2022
DOI: 10.1002/aenm.202200398
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Mechanistic Understanding of Lithium Deposition and Solid‐Electrolyte Interphase (SEI) Formation Using Advanced Characterization and Simulation Methods: Recent Progress, Limitations, and Future Perspectives

Abstract: In recent years, due to its great promise in boosting the energy density of lithium batteries for future energy storage, research on the Li metal anode, as an alternative to the graphite anode in Li‐ion batteries, has gained significant momentum. However, the practical use of Li metal anodes has been plagued by unstable Li (re)deposition and poor cyclability. Although tremendous efforts have been devoted to the stabilization of Li metal anodes, the mechanisms of electrochemical (re‐)deposition/dissolution of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 221 publications
(237 reference statements)
0
48
0
Order By: Relevance
“…Yang et al [ 33 ] reported that 2D MnZnO nanosheets/CNF infused with molten Li maintained 40 h at 50 mA cm −2 and 10 mAh cm −2 . Nevertheless, the modified Li anodes with high areal capacities (> 10 mAh cm −2 ) can only be performed (< 1000 h) at limited current densities (< 10 mA cm −2 ) [ 53 55 ]. Therefore, a rational design of lithiophilic material remains unclear for protecting Li metal anode toward practical application (especially at ultrahigh current density and areal capacity).…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al [ 33 ] reported that 2D MnZnO nanosheets/CNF infused with molten Li maintained 40 h at 50 mA cm −2 and 10 mAh cm −2 . Nevertheless, the modified Li anodes with high areal capacities (> 10 mAh cm −2 ) can only be performed (< 1000 h) at limited current densities (< 10 mA cm −2 ) [ 53 55 ]. Therefore, a rational design of lithiophilic material remains unclear for protecting Li metal anode toward practical application (especially at ultrahigh current density and areal capacity).…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] Moreover, the uncontrollable Li dendrites cause a series of issues such as severe volume changes, low Coulombic efficiency (CE) as well as poor cycle life, which impede the commercial application of Li anodes. [9][10][11][12] A large number of theoretical and experimental studies demonstrate that Li dendrite generation mainly originates from the inhomogeneous nucleation of metallic Li as well as the huge concentration gradient of lithium ion and nonuniform electric field. [13][14][15][16] Thus, Many strategies have been proposed to solve the intricate Li dendrite problems.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5–8 ] Moreover, the uncontrollable Li dendrites cause a series of issues such as severe volume changes, low Coulombic efficiency (CE) as well as poor cycle life, which impede the commercial application of Li anodes. [ 9–12 ]…”
Section: Introductionmentioning
confidence: 99%
“…Lithium metal batteries promise to be the future of battery technology with widespread use in nextgeneration electronic devices due to their low electrochemical potential (−3.04 V vs. standard hydrogen electrode) and high theoretical specific capacity (3,860 mAh g−1) [1][2][3] . A major technical problem associated with Li metal anodes, however, is the growth of dendrites, which leads to the formation of inactive Li during the plating and stripping process, resulting in poor cycle life, low coulombic efficiency (CE) as well as battery safety concerns [4][5][6] . To tackle the dendrite formation issue, researchers have proposed a wide range of solutions and strategies, from the use of various electrode designs and composite anodes to electrolyte engineering and interface modification, often including theoretical simulation methods [7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] A major technical problem associated with Li metal anodes, however, is the growth of dendrites, which leads to the formation of inactive Li during the plating and stripping process, resulting in poor cycle life, low coulombic efficiency (CE) as well as battery safety concerns. [4][5][6] To tackle the dendrite formation issue, researchers have proposed a wide range of solutions and strategies, from the use of various electrode designs and composite anodes to electrolyte engineering and interface modication, oen including theoretical simulation methods. [7][8][9][10] One promising approach that has recently gained attention is the use of threedimensional (3D) host structures to contain the Li metal anodes.…”
Section: Introductionmentioning
confidence: 99%